2012
DOI: 10.1186/1471-2229-12-139
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide mapping of NBS-LRR genes and their association with disease resistance in soybean

Abstract: BackgroundR genes are a key component of genetic interactions between plants and biotrophic bacteria and are known to regulate resistance against bacterial invasion. The most common R proteins contain a nucleotide-binding site and a leucine-rich repeat (NBS-LRR) domain. Some NBS-LRR genes in the soybean genome have also been reported to function in disease resistance. In this study, the number of NBS-LRR genes was found to correlate with the number of disease resistance quantitative trait loci (QTL) that flank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
128
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 149 publications
(135 citation statements)
references
References 27 publications
(36 reference statements)
5
128
1
1
Order By: Relevance
“…TIRonly and TIR-X sequences were not included in this study. For R-genes with CNV, the expression analysis result and related traits reported in previous studies [25][26][27][28][77][78][79] were listed in Supplementary Table 23. …”
Section: Methodsmentioning
confidence: 99%
“…TIRonly and TIR-X sequences were not included in this study. For R-genes with CNV, the expression analysis result and related traits reported in previous studies [25][26][27][28][77][78][79] were listed in Supplementary Table 23. …”
Section: Methodsmentioning
confidence: 99%
“…glycinea, sudden death syndrome and rust diseases, and nodulation in soybean (Ashfield et al, 2003;Zhu et al, 2010). We described an example of correlation between the NBS-LRR and disease resistance QTL, functional redundancy of disease resistance in soybean on recently duplicated regions harboring these genes as reported by Kang et al (2012).…”
Section: An Example: Study Of Association Between Nbs-lrr Genes and Rmentioning
confidence: 96%
“…Reports showed that some stress-responsive genes in plants were as tandem array, which might have been duplicated (Hanada et al, 2008;Zhang, 2003). Also, genes related to biotic stress response in A. thaliana (Maere et al, 2005) and disease resistance genes containing domain of a nucleotide-binding site and a leucine-rich repeat in soybean (Glycine max) (Kang et al, 2012;Shin et al, 2008) were well retained after the SSD and large scale duplication (LSD), suggesting their roles of adaptive evolution against environmental conditions. We highlighted an overview based on genome resources focusing on plant genome duplication which impacted to gene duplication with their related aspects to environmental changes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations